Improving Students’ Problem Solving Ability Through Learning Based Videoscribe - Yoga Budi Bhakti; Irnin Agustina Dwi Astuti; Eva Yuni Rahmawati (STKIP Singkawang, 2020)
The purpose of this research is to find out the problem-solving physics by using media-based videoscribe learning. Learning with the help of a video will make students more interactive and active because students can understand the concept of abstract and solve the problem of physics related to daily life. The method used in this research was the quasi-experimental method with the research design of The Randomized Post-Test Only Control Group Design, which involved 30 students as samples in Physics Education of Indraprasta PGRI University.The technique analysis of the research using the T-test. The results showed that by using learning media videoscribe could improve the ability of problem-solving physics. We found significant positive effects of the use of videoscribe in conveying physics lessons With the help of video scribe, learning is more efficient in physics learning. The students understand abstract physics material and are able to activate students in learning. These findings are consistent with studies on the improve of the student’s problem-sloving ability on physics learning.